COVID-19 pandemic in Malawi: Did public sociopolitical events gatherings contribute to its first-wave local transmission?. (May 2021) - Nyasulu, Juliet Charity Yauka; Munthali, Richard Junganiko; Nyondo-Mipando, Alinane Linda; Pandya, Himani; Nyirenda, Laywell; Nyasulu, Peter Suwirakwenda; Manda, Samuel
Highlights: The first wave of COVID-19 in Malawi coincided with widespread political gatherings. Mass gatherings and high-risk area repatriation were first wave main drivers. COVID-19 was more prevalent in older people, men and urban areas. Abstract: Introduction: The COVID-19 pandemic in Malawi emerged amidst widespread anti-government demonstrations and subsequent mass gatherings. This paper describes the incidence and factors associated with the spread of the COVID-19 pandemic in Malawi. Methodology: This was a retrospective study of public data analysing geopolitical and immigration activities that occurred between 02 April and 08 September 2020. The Chi-square test of independence was used to tabulate sex and age-related fatality ratios among deaths due to COVID-19-related complications. Results: The drivers for COVID-19 spread were mass gatherings secondary to the country's political landscape and repatriation of citizens from high-risk areas coupled with minimum use of public health interventions. The prevalence was higher in people aged 50–59 years, males and in urban areas. Men had an increased risk of COVID-19-related deaths (Case Fatality Ratio: 1.58 (95% CI 1.11–2.22) compared with women. Furthermore, men and women aged ≥40 years were 16.1 times and 7.1 times more likely to die of COVID-related complications, respectively. Men aged ≥40 years had a 62% increased risk of deaths compared with women of the same age group. Conclusion: Mass political gatherings and cross-border immigration from high-risk areas were drivers for infection. Males, older age and urban residence were associated with increased COVID-19 morbidity and mortality. To control the spread of COVID-19 there is a need to regulate mass gatherings and repatriation of citizens, and strengthen the use of preventive health interventions. Men, the older age groups and urban areas should be prioritised for COVID-19 prevention strategies.